2011
DOI: 10.1021/ic2015308
|View full text |Cite
|
Sign up to set email alerts
|

Existence of Two Concomitant Magnetic Structures Below TNéelfor the Natrochalcite, NaFeII2(H3O2)(MoO4)2

Abstract: A comparative study of the magnetic properties and magnetic structures of the natrochalcite, NaFe(2)(D(3)O(2))(MoO(4))(2) (FeD) to those of the isostructural NaCo(2)(D(3)O(2))(MoO(4))(2) (CoD) and NaNi(2)(D(3)O(2))(MoO(4))(2) (NiD) is presented. The structural change is a shrinking of the unit cell in the order of the ionic radii of the transition metal, FeD> CoD > NiD. While NiD and CoD are canted-antiferromagnets with T(N) = 28 and 21 K, respectively, FeD is an anisotropic 2D-Ising antiferromagnet (T(N) = 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…The first of these sets are canted antiferromagnets, the second are ferrimagnets, and the last are ferromagnets. The last family of compounds that we are studying is that of natrochalcite, AM 2 (H 3 O 2 )(TO 4 ) 2 . , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first of these sets are canted antiferromagnets, the second are ferrimagnets, and the last are ferromagnets. The last family of compounds that we are studying is that of natrochalcite, AM 2 (H 3 O 2 )(TO 4 ) 2 . , …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and crystal chemistry using X-ray, and in some cases neutron diffraction, of the mineral natrochalcite, AM 2 (H 3 O 2 )(TO 4 ) 2 , family are well documented, but their magnetic properties and magnetic structures remained unknown until the reported antiferromagnetism of NaCu 2 (D 3 O 2 )(SO 4 ) 2 ( T N = 3.3 K) and NaM 2 (H 3 O 2 )(MoO 4 ) 2 (M = Ni ( T N = 21 K) and Co ( T N = 28 K)). , Previous works were concerned principally with the syntheses, characterization, and identification of the geometry and function of the H 3 O 2 anion. It has been demonstrated that a wide range of salts can be prepared with A of varying sizes (Na, K, Cs, Rb, Tl, NH 4 , and Ag), M of the divalent transition metals (Mn, Fe, Co, Ni, Cu, and Zn), and the central atom of the tetrahedral anion (T) being S, Se, or Mo. Although the known salts contain principally divalent metals, one has been reported to contain trivalent iron. Such a variety of possible cations (A, M, and T) in the three crystallographic sites provide a handful of materials for systematically studying their influence on the magnetic properties and magnetic structures as a function of cationic sizes, spin, and magnetic anisotropy. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Thus, it is highly unlikely that a crystalline magnetic solid can exhibit two widely different magnetic structures simultaneously. Nevertheless, precisely such an observation has been reported for NaFe 2 (H 3 O 2 )(MoO 4 ) 2 , 3 and the cause for this phenomenon has not been understood yet. In this Communication, we explore the reason for this finding on the basis of density functional theory (DFT) calculations to find that the chemically meaningful structures of NaFe 2 (H 3 O 2 )(MoO 4 ) 2 require the partitioning of H 3 O 2 units into H 2 O and HO groups and that the spin exchanges of the resulting structures depend on the H-atom distributions, although the Fe/O framework remains unchanged.…”
mentioning
confidence: 99%
“…It is remarkable that the intrachain Fe−O−Fe superexchange is AFM in the q 2 structure but is FM in the q 1 structure, despite the fact that the Fe/O framework is identical in both structures. Because ∠Fe−O−Fe of the edge-sharing FeO 4 chains is considerably greater than 90°(i.e., 98.8°), 3 one would have expected that the FeO 4 chains should be AFM chains on the basis of the Goodenough rule. 4 This is not true for the q 1 structure.…”
mentioning
confidence: 99%